2019
DOI: 10.7249/rr2912
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Scientific Research: An Examination of Ethical Principles and Emerging Topics

Abstract: Limited Print and Electronic Distribution Rights This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Respect for communities allows a broadening of this concept to include a variety of cultural norms, including those which place less emphasis on individual autonomy and autonomous decision-making than is the norm in some cultures 54. Procedural principles to help with respecting persons and communities include, for example, the need for trustworthiness, transparency, privacy and ownership, accountability, autonomy, engagement, the need for consent, and the right to withdraw 36 51 53. Respect for the environment includes taking environmental destruction into consideration by considering the environmental impacts associated with the research endeavour, particularly when that destruction occurs in places which may not directly benefit from the outputs, for example, clinical trials in the developing world, or in places where natural resources are used, not replenished and not properly compensated for (eg, harvesting of medicinal plants in a rainforest, mining).…”
Section: A Research Ethics Framework Based On Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Respect for communities allows a broadening of this concept to include a variety of cultural norms, including those which place less emphasis on individual autonomy and autonomous decision-making than is the norm in some cultures 54. Procedural principles to help with respecting persons and communities include, for example, the need for trustworthiness, transparency, privacy and ownership, accountability, autonomy, engagement, the need for consent, and the right to withdraw 36 51 53. Respect for the environment includes taking environmental destruction into consideration by considering the environmental impacts associated with the research endeavour, particularly when that destruction occurs in places which may not directly benefit from the outputs, for example, clinical trials in the developing world, or in places where natural resources are used, not replenished and not properly compensated for (eg, harvesting of medicinal plants in a rainforest, mining).…”
Section: A Research Ethics Framework Based On Sustainabilitymentioning
confidence: 99%
“…35 At the same time, a recent review of international research ethics frameworks by RAND suggests that such environmental concerns are primarily applied in non-human-centric disciplines; within human participant research, harm is generally considered anthropocentrically in human terms only. 36 If moral reflections are to consider the environment, key unanswered questions include how we should give respect to non-human worlds, especially since human endeavours will always inevitably lead to the destruction of at least some of the biotic community and ecosystems, and how this respect should or could be weighed next to humans (p235). 37 [ iii] Despite this, moral obligations to the environment still exist, even if they are anthropocentric and instrumentalising for reasons of self-preservation.…”
Section: Environment and (Bio)ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, physical or mental integrity was not compromised (Fouka & Mantzorou, 2011). Since the desire to participate in research is subject to informed consent and agreement (Weinbaum et al, 2019), the principle of autonomy was also taken into account. Finally, the study raised the information in a confidential manner so that the information obtained (demographic information) was not sent to third parties, but only for learning purposes.…”
Section: Ethical Criteriamentioning
confidence: 99%
“…Ethics can be defined as "well-founded standards of right and wrong that prescribe what humans ought to do, usually in terms of rights, obligations, benefits to society, fairness, or specific virtues" (Velasquez et al, 2010). In a review of ethics in scientific research, Weinbaum et al (2019) identified 10 ethical principles common across scientific disciplines: (1) duty to society; (2) beneficence; (3) avoiding conflict of interest; (4) informed consent; (5) integrity; (6) non-discrimination; (7) nonexploitation; (8) privacy and confidentiality; (9) professional competence; (10) professional discipline. We believe that the conduct of ocean science activates a duty to society for researchers because their research is either funded by or providing results of interest to the public.…”
Section: The Ethical Chargementioning
confidence: 99%